Development and validation of age- and sex-specific reference intervals for serum vitamin B5 in Henan pediatric population by LC-MS/MS - Luan, Yusheng; Li, Tiewei; Lin, Fatao; Li, Xiaojuan; Yang, Junmei (Frontiers in Nutrition, 2025)
Background and objectiveReference intervals (RIs) for serum vitamin B5 (pantothenic acid, B5) specific to the Henan pediatric population have not been established. Current clinical practice, in China continues to rely on reference thresholds derived from international populations. However, these generalized intervals may lack diagnostic accuracy and relevance when applied to domestic children. This study aims to establish age- and sex-specific RIs for serum B5 in Henan children aged 1–17 years, thereby enhancing the reliability of clinical assessments and nutritional evaluations.MethodsThis cross-sectional study involved 1,998 healthy children who underwent routine physical examinations between January 2022 and March 2025. Serum B5 concentrations were quantified using liquid chromatography–tandem mass spectrometry (LC–MS/MS) system. Data exhibiting non-normal distribution are expressed as median and interquartile range (IQR) [M (P25, P75)]. Age- and sex-related differences were analyzed using the Mann–Whitney U test or Kruskal–Wallis test, as appropriate. RIs validation was performed using a subsequent cohort (n = 547) examined from March to May 2025.ResultsAge and sex were identified as significant factors influencing serum B5 concentrations in the pediatric cohort. The study population had a predominance proportion of male participants (59.01%, 1,179/1,998), and most subjects were under the age of 12, reflecting a primarily prepubescent sample (93.59%, 1,870/1,970). Based on these demographic characteristics, further stratified analyses were conducted to establish age- and sex-specific RIs for serum B5 levels. For male children, the RIs were 31.57–169.31 ng/mL for the 1–5-year age group, 24.23–127.57 ng/mL for those aged 6–11 years, and 25.36–95.37 ng/mL for those aged 12 and older. Female participants showed RIs of 31.10–166.20 ng/mL, 23.93–114.79 ng/mL, and 18.56–122.55 ng/mL for the same age categories. These stratified intervals highlight the importance of considering both age and sex in the clinical interpretation of pediatric B5 measurements. Validation results confirmed the reliability of the established reference intervals, demonstrating a minimum conformity rate of 93.94%, which meets the 90% threshold stipulated by Chinese industry standards.ConclusionThis study provides the first comprehensive set of age- and sex-specific RIs for serum B5 in Chinese children aged 1–17 years and has validated them in a representative cohort.